PARADOXICAL REPRESENTATION OF FEMALE NARATION IN THE SPIRIT OF MAK UNGKAI STORY - Tomi Arianto; Simanjuntak Sapta Dairi (Universitas Putera Batam, 2019)
The story of Mak Ungkai sea ghost is very commonly heard by old generation of Malay people in Batam coast. The sea ghost portrayed as a scary female ghost, disturbing humans, sinking fishing boats, and harassing coastal people. On the other hand, researchers suspected a paradoxical narrative of Mak Ungkai character which is relatively close to nature, preserves the environment, and counter-patriarch. This problem directed to examine more deeply the image of women in this phenomenon to reveal the interpretation behind the story. This research used an ecofeminist approach with the aim of reversing the stereotypes of women narrated by the community against the character of Mak Ungkai and its relation to the environment and nature. According to Shiva (1998), ecocritic is a new cosmology that views nature and women as having relationships that maintain, cooperate and protect one another. By using descriptive qualitative method, researchers collected data in depth interviews and immediately plunged into the community. Interviews were conducted directly with 5 speakers from the indigenous Malay community in Sebulang Island, Batam. The research used recordings and cameras which are then transcribed in narrative texts that are easily understood. The results of the study found that (1) the existence of patriarchal stereotypes through mak ungkai sea ghost story (2) the paradoxical representation of women based on ecofeminist framework behind the story.